Applications of Magnetosomes Synthesized by Magnetotactic Bacteria in Medicine - Alphandéry, Edouard (Frontiers in Bioengineering and Biotechnology, 2014)
Magnetotactic bacteria belong to a group of bacteria that synthesize iron oxide nanoparticles covered by biological material that are called magnetosomes. These bacteria use the magnetosomes as a compass to navigate in the direction of the earth’s magnetic field. This compass helps the bacteria to find the optimum conditions for their growth and survival. Here, we review several medical applications of magnetotactic bacteria and magnetosomes, such as those in magnetic resonance imaging (MRI), magnetic hyperthermia and drug delivery. DWe describe different methods that can be used to prepare the magnetosomes for these applications are described. TWe also summarize the toxicity and biodistribution results that have been published are summarized., They showing that the magnetosomes can be safely used provided that they are prepared in specific conditions. TWe also highlight the advantageous properties of the magnetosomes compared with those of chemically synthesized nanoparticles of similar composition are also highlighted.